ANALISIS FAKTOR – FAKTOR YANG MEMPENGARUHI VOLUME PENJUALAN MINYAK SAWIT PTPN III (PERSERO) TAHUN 2010 – 2015 The Analysis Of Affect Factors The Sales Volume in Palm Oil PTPN III (Persero) in 2010-2015 - Purjianto Purjianto; Alda Kartika (Institut Teknologi Sawit Indonesia, 2017)
This research is based on the importance of palm oil as a raw material for cooking oil for household consumption so it is an opportunity for palm oil producers to increase sales of palm oil. The sales volume of palm oil is strongly influenced by Land Area, FFB Production, Palm Oil Production and Palm Oil Price. These conditions, palm oil producers are required to attented to the above factors to achieve the target as a market leader in palm oil sales nationally. This research is descriptive using secondary data with research location in PTPN III (Persero) Medan. The method of analysis used is quantitative analysis that is multiple regression analysis. From the results of the analysis obtained regression equation Y = 40,6550 + 10,686 X1 + 1,928 X2 + 6,488 X3 + 67,886 X4 + e, where Variable Price Palm Oil has the biggest influence to Palm Oil Sales Volume of 67,886, then followed by Variable Area Land of 10,686, Palm Oil Production Variable equal to 6,488 and Variable of FFB Production equal to 1,928. Hypothesis testing using t test shows that the four independent variables were Area (X1), Production of FFB (X2), Palm Oil Production (X3) and Palm Oil Price (X4) studied proved positive relationship but not significantly affect the dependent variable buying decision. Thenthe F-test can be known that proved to be a positive relationship but not significantly affect the dependent variable that is Palm Oil Sales Volume. Adjusted R Square figures show that 82.10% of variation in Palm Oil Sales Volume can be explained by the four independent variables in multiple regression equations. While the rest of 17.90% explained by other variables out of the four variables used in this research.